Exploring the Role of Game-Based Learning in Early Childhood Cognitive Development: Perspectives from Teachers and Parents - Hibana, Hibana; Rahman Nayla, Muthia; Nurhayati, Kulsum (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
Game-based learning is increasingly recognized as an effective approach to fostering cognitive development in early childhood. This study examines how it enhances children's problem-solving, memory, and attention, as well as teachers' and parents' perceptions of its implementation. Using a qualitative case study approach, data were collected from 20 teachers and 15 parents through semi-structured interviews, classroom observations, and document analysis. Thematic analysis revealed that game-based learning promotes cognitive development by encouraging active engagement, fostering curiosity, and improving problem-solving and information retention. Teachers highlighted the importance of designing meaningful play experiences, while parents observed improvements in children's focus and memory. However, challenges such as inadequate teacher training, limited play resources, and low parental awareness hinder optimal implementation. Findings suggest that successful game-based learning requires well-structured activities, professional development for educators, and greater parental involvement. Addressing these challenges through targeted interventions could enhance its effectiveness in early childhood education. This study provides valuable insights into teachers’ and parents’ perceptions of play-based learning in cognitive development and underscores the need for collaborative efforts to maximize its potential. Future research should explore its long-term impacts and strategies for integrating it into diverse educational settings.